Reframing Happiness: The Effect of Mindfulness Practice on Adolescent Subjective Well-Being - Azizah, Nisa’ul; Laily, Nadhirotul (Psikoborneo: Jurnal Ilmiah Psikologi, 2025)
Adolescents are a vulnerable age group who often experience various emotional and social pressures, making subjective well-being an important aspect to consider in supporting their development. One of the factors assumed to play a role in enhancing subjective well-being is mindfulness, defined as full awareness of the present moment without judgment. This study aimed to determine the influence of mindfulness on subjective well-being among adolescents. The method used was a quantitative correlational approach with simple regression analysis, involving 89 adolescents selected through saturated sampling technique. The instruments used included a mindfulness scale and a subjective well-being scale, both of which had been tested for validity and reliability. The results of the study showed that there was no significant influence between mindfulness and subjective well-being, indicated by a determination coefficient value of 0.0034 or a contribution of only 0.34%, as well as an F-test result that was lower than the F-table value. These findings indicated that other factors such as social support, self-esteem, or emotion regulation may play a more substantial role in shaping adolescents’ subjective well-being. The implication of this study highlighted the importance of developing adolescent well-being enhancement programs that not only focus on mindfulness but also consider psychosocial and environmental factors relevant to the adolescent developmental phase. Remaja merupakan kelompok usia yang rentan mengalami berbagai tekanan emosional dan sosial sehingga kesejahteraan subjektif (subjective well-being) menjadi aspek penting untuk diperhatikan dalam mendukung perkembangan mereka. Salah satu faktor yang diduga berperan dalam meningkatkan subjective well-being adalah mindfulness atau kesadaran penuh terhadap momen saat ini tanpa penilaian. Penelitian ini bertujuan untuk mengetahui pengaruh mindfulness terhadap subjective well-being pada remaja. Metode yang digunakan adalah kuantitatif korelasional dengan pendekatan regresi sederhana, melibatkan 89 remaja sebagai subjek penelitian yang dipilih melalui teknik sampling jenuh. Instrumen yang digunakan meliputi skala mindfulness dan skala subjective well-being yang telah melalui uji validitas dan reliabilitas. Hasil penelitian menunjukkan bahwa tidak terdapat pengaruh signifikan antara mindfulness dan subjective well-being, ditunjukkan dengan nilai koefisien determinasi sebesar 0,0034 atau kontribusi hanya 0,34% serta hasil uji F yang lebih kecil dari F tabel. Temuan ini mengindikasikan bahwa faktor lain seperti dukungan sosial, self-esteem, atau regulasi emosi mungkin lebih berperan dalam membentuk kesejahteraan subjektif remaja. Implikasi dari penelitian ini menunjukkan pentingnya mengembangkan program peningkatan kesejahteraan remaja yang tidak hanya berfokus pada mindfulness, tetapi juga memperhatikan faktor psikososial dan lingkungan yang relevan dengan fase perkembangan remaja.